Marketing boards and ministers : a study of agricultural marketing boards as political and administrative instruments - Giddings, Philip James (Farnborough, Hants. (D.C. Heath Ltd, Westmead, Farnborough, Hants.) : Saxon House ; Lexington, Mass. : Lexington Books, 1974)
This book deals with one particular variety of the bewildering range of organisations in modern Britain which go under the title public bodies. These organisations provide services on behalf of the Government therefore the book examines the relationship they had with the government as well as they board membership, finance, statutory control and policy problems.
Includes index
Includes bibliographical references and index.
usc 22/01/2019
Loans
Keywords: Marketing boards; Agriculture and state; Administrative agencies